Emerging resistance of higher antimicrobials and growing sensitivity of old antimicrobials against existing infections in burns - Lunawat, Ajay; Sharma, Rajesh; Kolla, Venkatesh; Patel, Shailendra (International Surgery Journal, 2016)
Background: The widespread resistance of microorganisms to antibiotics threatens to be a future medical disaster. Antimicrobial resistance among a wide variety of human bacterial and fungal burn wound pathogens, particularly nosocomial isolates, limits the available therapeutic options for effective treatment of burn wound infections Objective: To analyze the emergence of resistance to higher group of antibiotics and shift of sensitivity towards older group of antibiotics. Methods:The microbial colonization of wounds was studied from day of admission to date of discharge or date of expiry (2011-2014). The sampling included swabs taken from clinically deep areas of burn wounds prior to cleaning. Culture and sensitivity reports of urine, central line, bronchoscopic suction, catheter tips were not included in samples. Tissue biopsy during excision was included in the samples. Analysis done with the help of Chi-square test. Results:Initially after burn injury there is predominance of staphylococcal group followed by gram negative organism, after which there is a predominance of gram negative organism. In this study we observed an increase in resistance to higher group of antibiotics like imipenem (p>0.005) and increased susceptibility to polymyxin group of drugs (p<0.005). Conclusions:It suggests that prevention is better than cure. Developing resistance can be prevented by misuse of antibiotics, premature change of antibiotics and prevention of cross contamination. For effective prevention of developing resistance to higher antibiotics the burn centres should look in and bring a strict antibiotic policy.